A Child with Multiple Congenital Malformations and a 46, XX, t(Bq+;Dq−)/45, XX, −B, −D, + der(B), t(Bq+;Dq−) Karyotype. Issue 4 (December 1973) - Carnevale, Alessandra; Cobos, Luis De Los
Abstract : A case of a female infant with malformations of upper extremities and mental and growth retardation is reported. The karyotype showed a 46, XX, t(Bq+;Dq−)/45, XX, −B, −D, +der(B), t(Bq+;Dq−) mosaicism. The clinical findings in relation to the long arm deletion of a B-group chromosome are discussed.